1995
DOI: 10.1101/gad.9.7.808
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific and allele-specific replication timing control in the imprinted human Prader-Willi syndrome region.

Abstract: To examine the relationship between replication timing and differential gene transcription in tissue-specific and imprinted settings we have studied the replication timing properties of the human Prader-Willi syndrome (PWS) region on human chromosome 15q11-13. Interphase fluorescence in situ hybridization with an overlapping series of cosmid clones was used to map a PWS replication timing domain to a 500-to 650-kb region that includes the SNRPN gene. This PWS domain replicates late in lymphocytes but predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 38 publications
4
49
0
1
Order By: Relevance
“…A variety of investigations have confirmed the association between the replication timing of a locus and its transcriptional activity (23)(24)(25). Expressed loci have been found to replicate early in S phase, whereas nonexpressing loci replicate late in S phase.…”
Section: Discussionmentioning
confidence: 94%
“…A variety of investigations have confirmed the association between the replication timing of a locus and its transcriptional activity (23)(24)(25). Expressed loci have been found to replicate early in S phase, whereas nonexpressing loci replicate late in S phase.…”
Section: Discussionmentioning
confidence: 94%
“…Using this method it was clearly shown that a pair of alleles which are known to be expressed concomitantly replicate synchronously, [10][11][12][13] whilst alleles subjected to some mechanism leading to alelle-specific expression, such as imprinting, 11,[14][15][16] X chromosome inactivation, 12 or some other allelic inactivation, 13,17 replicate asynchronously.…”
Section: Introductionmentioning
confidence: 99%
“…The leading candidate is DNA methylation that is established in different patterns in the male and female germ lines and is maintained throughout embryogenesis to regulate the imprinted state. There are other epigenetic differences between the parental alleles of imprinted genes, including differential sensitivity of chromatin to nuclease digestion, asynchronous replication, and differential frequencies of meiotic recombination (5,13,18,24,25,39), but these are thought to be the consequences of the primary epigenetic mark, not the causes.…”
mentioning
confidence: 99%